Pulses for Nutrition in India: Changing Patterns from Farm to Fork - Devesh Roy (Agricultural Economics Research Review, 2023)
Pulses for Nutrition in India: Changing Patterns from Farm to Fork, edited by Devesh Roy, P K Joshi and Raj Chandra, International Food Policy Research Institute, Washington DC, USA, pp. xxvi+256.